Digital Divide: Determinants and Policies with Special Reference to Asia - M. G. Quibria; Shamsun N. Ahmed; Ted Tschang; Mari-Len Reyes-Macasaquit (Asian Development Bank (ADB), 2002)
"Access to new information and communication technologies (ICT) remains extremely unequally distributed across and within societies. While there have been a good deal of popular discussions about this "digital divide", not much is known about the quantitative significance of its various determinants. By undertaking a set of crosscountry regressions, the paper finds that income, education, and infrastructure play a critical role in shaping the divide. Based on this analysis, the paper also offers some policy suggestions as to how to promote wider diffusion of ICT in poorer societies."
hdl:11540/1935
Keywords: 330; Informationstechnik; Innovationsdiffusion; Nationaleinkommen; Bildungsniveau; Infrastruktur; Technologiepolitik; Asien; Digitale Spaltung